Key indicators for guiding tocilizumab therapy to prevent orbital decompression surgery in hormone-resistant dysthyroid optic neuropathy - Shu, Wenjun; Yan, Mingxu; Gan, Lu; Li, Lu; Tao, Hongyue; Peng, Zhiyu; Wang, Jinghan; Li, Xiaofeng; Lin, Xintong; Chen, Haifeng; Guo, Jie; Xue, Kang; et al. (Frontiers in Immunology, 2025)
IntroductionTocilizumab (TCZ) has been demonstrated to be effective in treating thyroid-associated ophthalmopathy (TAO); however, its efficacy in hormone-resistant dysthyroid optic neuropathy (DON) remains unclear. This study aims to identify baseline and post-treatment indicators that can predict the necessity for surgical intervention following TCZ therapy.MethodsThirty-one hormone-resistant DON patients treated with TCZ were categorized into surgery (n=15, 7 males, 8 females) and non-surgery (n=16, 8 males, 8 females) groups based on their post-TCZ surgical status. Retrospective comparisons between the two groups were performed using pre- and post-treatment ophthalmic assessments, biomarkers, and orbital magnetic resonance imaging (MRI) scans. The predictive value of identified variables was evaluated through receiver operating characteristic (ROC) curve analysis and logistic regression analysis.ResultsThe surgery group exhibited a significantly higher baseline thyroid-stimulating hormone receptor antibody (TRAb) (P=0.001) and a positive change in the maximal signal intensity ratio of extraocular muscle to temporalis muscle (SIR(EOM/temporalis)MAX), whereas the non-surgery group demonstrated a negative change (P<0.001). A TRAb cut-off value of ≤5.07 IU/L predicted non-surgery with 93.3% sensitivity and 81.2% specificity, while a SIR(EOM/temporalis)MAX cut-off value of ≤-1.83 had 86.7% sensitivity and 87.5% specificity. The area under the curve was 0.846 for TRAb and 0.863 for SIR(EOM/temporalis)MAX. Multivariate regression confirmed SIR(EOM/temporalis)MAX change (P=0.017) as an independent predictor of surgical intervention. Linear regression revealed a significant correlation between SIR(EOM/temporalis)MAX change and TCZ dosage in the non-surgery group (P=0.005), but not in the surgery group.DiscussionThe percentage change in SIR(EOM/temporalis)MAX following TCZ treatment and baseline TRAb can serve as predictors of the necessity for surgical intervention in hormone-resistant DON. These indicators assist in the personalization of TCZ therapy and in the avoidance of unnecessary surgical procedures.